Association of Trimethylamine N-Oxide and Its Precursor With Cerebral Small Vessel Imaging Markers - Chen, Yiyi; Xu, Jie; Pan, Yuesong; Yan, Hongyi; Jing, Jing; Yang, Yingying; Wang, Xing; Wan, Huijuan; Gao, Ying; Han, Shangrong; Zhong, Xi; Liu, Chenhui; et al. (Frontiers in Neurology, 2021)
Background: High plasma levels of trimethylamine N-oxide (TMAO) and its precursor choline have been linked with stroke; however, their association with cerebral small vessel disease remains unclear. We evaluated here the association of plasma levels of TMAO and choline with imaging markers of cerebral small vessel disease, including white matter hyperintensities, lacunes, and cerebral microbleeds. Methods: We performed a baseline cross-sectional analysis of a multicenter hospital-based cohort study from 2015 to 2018. The data were collected from 30 hospitals in China and included 1,098 patients with ischemic stroke/transient ischemic attack aged ≥18 years. White matter hyperintensities, lacunes, and cerebral microbleeds were evaluated with the patients’ demographic, clinical, and laboratory information removed. White matter hyperintensities were rated using the Fazekas visual grading scale, while the degree of severity of the lacunes and cerebral microbleeds was defined by the number of lesions. Results: Increased TMAO levels were associated with severe white matter hyperintensities (adjusted odds ratio [aOR] for the highest versus lowest quartile, 1.5; 95% confidence interval [CI], 1.0 to 2.1, p = 0.04). High TMAO levels were more strongly associated with severe periventricular white matter hyperintensities (aOR for the highest versus lowest quartile, 1.6; 95% CI, 1.1 to 2.3, p = 0.009) than deep white matter hyperintensities (aOR for the highest versus lowest quartile, 1.3; 95% CI, 0.9 to 1.9, p = 0.16). No significant association was observed between TMAO and lacunes or cerebral microbleeds. Choline showed trends similar to that of TMAO in the association with cerebral small vessel disease. Conclusions: In patients with ischemic stroke or transient ischemic attack, TMAO and choline appear to be associated with white matter hyperintensities, but not with lacunes or cerebral microbleeds; TMAO and choline were associated with increased risk of a greater periventricular, rather than deep, white matter hyperintensities burden.